2013
DOI: 10.7251/agren1303449m
|View full text |Cite
|
Sign up to set email alerts
|

Crop Diversification Affects Biological Pest Control

Abstract: Crop monocultures encourage the multiplication and spread of pest insects on massive and uniform crop. Numerous studies have evaluated the impact of plant diversification on pests and beneficial arthropods population dynamics in agricultural ecosystems and provided some evidence that habitat manipulation techniques like intercropping can significantly influence pest control. This paper describes various potential options of habitat management and design that enhance ecological role of biodiversity in agroecosy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 55 publications
1
3
0
Order By: Relevance
“…Sandalwood grown with five plant species viz., Cajanus cajan + Tectona grandis + Mangifera indica + Citrus reticulata +Punica granatum, with four plant species viz., Coffea arabica + C. robusta + Greviliea robusta + Piper betel and among the combinations with three plant species, viz., Macrotyloma uniflorum, Punica granatum and Mangifera indica did not necessitate any insecticidal spray. This confirms the fact that presence of natural enemies play important role in suppression of herbivores inagro-ecosystems (Marković, 2013). The findings demonstrated that habitat diversification in growing sandalwood is an ideal option to manage the insect pest problems without use of any insecticide.…”
Section: Resultssupporting
confidence: 81%
“…Sandalwood grown with five plant species viz., Cajanus cajan + Tectona grandis + Mangifera indica + Citrus reticulata +Punica granatum, with four plant species viz., Coffea arabica + C. robusta + Greviliea robusta + Piper betel and among the combinations with three plant species, viz., Macrotyloma uniflorum, Punica granatum and Mangifera indica did not necessitate any insecticidal spray. This confirms the fact that presence of natural enemies play important role in suppression of herbivores inagro-ecosystems (Marković, 2013). The findings demonstrated that habitat diversification in growing sandalwood is an ideal option to manage the insect pest problems without use of any insecticide.…”
Section: Resultssupporting
confidence: 81%
“…Olfactory cues emanating from large-scale monoculture agricultural crops would rapidly become ubiquitous in the local environment, leading to sensitization for host odors and creating an ideal setting for learned acceptance by polyphagous insects (Smith and McSorley 2000, Potter and Held 2002, Teasdale et al 2004, Marković 2013). Homogeneous forests due to replanting by commercial forestry industry pose a similar risk for learning by potential forest pest species (Jactel et al 2005).…”
Section: Challenges Associated With Insect Learning and Pest Managementmentioning
confidence: 99%
“…Managing plant diversity is one of the main strategies to achieve sustainability in agricultural systems (MARKOVIC, 2013). Intercropping is one of the practices for this diversification, and the most accessible and suitable managements for vegetable crops (MONTEZANO;PEIL, 2006).…”
Section: Introductionmentioning
confidence: 99%